2015
DOI: 10.1021/acs.langmuir.5b01992
|View full text |Cite
|
Sign up to set email alerts
|

Gelled Lyotropic Liquid Crystals

Abstract: In our previous work we were able to prove that gelled bicontinuous microemulsions are a novel type of orthogonal self-assembled system. The study at hand aims at complementing our previous work by answering the question of whether gelled lyotropic liquid crystals are also orthogonal self-assembled systems. For this purpose we studied the same system, namely, water-n-decane/12-hydroxyoctadecanoic acid (12-HOA)-n-decyl tetraoxyethylene glycol ether (C10E4). The phase boundaries of the nongelled and the gelled l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
1
24
1
1
Order By: Relevance
“…Gelled lyotropic liquid crystals can also be obtained by adding an appropriate LMG to al yotropic liquid crystal. [43] This study was carried out with the system used for the investigation of the gelled bicontinuous microemulsion since lyotropic liquid crystals were observed at higher surfactant concentrations in this system. Thep hase boundaries of the non-gelled and the gelled lyotropic LCs were determined visually and by 2 HNMR spectroscopy,a nd it was found that the general pattern of the phase diagram is not altered if one adds the gelator.…”
Section: Gelled Lyotropic Liquid Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelled lyotropic liquid crystals can also be obtained by adding an appropriate LMG to al yotropic liquid crystal. [43] This study was carried out with the system used for the investigation of the gelled bicontinuous microemulsion since lyotropic liquid crystals were observed at higher surfactant concentrations in this system. Thep hase boundaries of the non-gelled and the gelled lyotropic LCs were determined visually and by 2 HNMR spectroscopy,a nd it was found that the general pattern of the phase diagram is not altered if one adds the gelator.…”
Section: Gelled Lyotropic Liquid Crystalsmentioning
confidence: 99%
“…Gelled lyotropic liquid crystals can also be obtained by adding an appropriate LMG to a lyotropic liquid crystal . This study was carried out with the system used for the investigation of the gelled bicontinuous microemulsion since lyotropic liquid crystals were observed at higher surfactant concentrations in this system.…”
Section: Gelled Complex Fluidsmentioning
confidence: 99%
“…Gelierte lyotrope Flüssigkristalle können ebenfalls gewonnen werden, indem man zu einem lyotropen Flüssigkristall einen geeigneten niedermolekularen Gelator hinzufügt . Diese Studie wurde mit dem System durchgeführt, das auch für die Untersuchung der gelierten bikontinuierlichen Mikroemulsion verwendet wurde, weil bei höheren Tensidkonzentrationen in diesem System lyotrope Flüssigkristalle beobachtet wurden.…”
Section: Gelierte Komplexe Fluideunclassified
“…Another approach, the physicochemical approach, utilizes the solubilization function of the surfactants and does not depend on the specific chemical properties of the gelators. A bicontinuous microemulsion (BME) and lamellar liquid crystal (L α ) phase formed by a water/surfactant/oil system can solubilize 12-HOA at high temperature, and the gels are obtained by cooling [22][23][24][25][26][27][28]. In this case, the afforded gel is not purely a hydrogel because it contains micro-oil domains of BME or L α .…”
Section: Introductionmentioning
confidence: 99%